Analysis of Relationship between Religious Knowledge, Attitude, and Behaviour of Islamic Universities Female Students towards the Halalness of Cosmetic and Wear Products - Suri, Fraulein Intan; Iwansyah, Henry (Universitas Islam Negeri Raden Intan Lampung, 2024)
This research describes and analyzes the relationship between religious knowledge and the attitudes and behavior of State Islamic Universities (PTKIN) female students in purchasing cosmetics and wearing products that have not been halal (religiously permitted). The aim is to analyze students' tendencies, attitudes, and behavior when consuming cosmetics and consumer goods. Research data was obtained through interviews and distributing questionnaires to three campuses, namely: UIN Raden Intan Lampung, UIN Walisongo Semarang, and UIN Sunan Gunung Djati Bandung. The data were then processed and analyzed using qualitative and quantitative analysis techniques. This research found an inconsistency between students' cognitive, affective, and psychomotor aspects in deciding to buy/use cosmetics and wear products whose halalness is still unclear. This inconsistency is mainly due to the scarcity of products labeled halal and the difficulty of knowing the ingredient composition of the products offered. This research concludes a significant correlation between the religious background knowledge of female students and their attitudes and behavior toward the halalness of cosmetic and wear products.